Aging and intellectual disability: Insights from mouse models of down syndrome. Issue 1 (16th August 2013) - Ruparelia, Aarti; Pearn, Matthew L.; Mobley, William C.; Silverman, Wayne; Mailick, Marsha R.
<x xml:space="preserve">Abstract</x> Down syndrome (DS) is one of many causes of intellectual disability (ID), others including but not limited to, fetal alcohol syndrome, Fragile X syndrome, Rett syndrome, Williams syndrome, hypoxia, and infection. Down syndrome is characterized by a number of neurobiological problems resulting in learning and memory deficits and early onset Alzheimer's disease. The cognitive impairment in people with DS is virtually universal but varies considerably with respect to expressivity and severity. Significant advances in medical treatment and social inclusion have increased longevity in people with DS resulting in an increased aging population, thus highlighting the significance of early onset of dementia and the importance of identifying pharmacotherapies to treat DS‐associated health complications in adults. Given its prevalence and established mouse models, this review will focus on ID in the DS population; specifically, the superimposed effect of aging on the complications already manifest in DS adults and the cognitive insights gained from studies on mouse models of DS. © 2013 Wiley Periodicals, Inc. Dev Disabil Res Rev 2013;18:43–50